2021
DOI: 10.1002/ejp.1789
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experimental and clinical musculoskeletal pain on spinal and supraspinal projections to motoneurons and motor unit properties in humans: A systematic review

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 93 publications
(251 reference statements)
3
19
1
Order By: Relevance
“…Previous investigations [ 12 , 13 ] with AAS patients found neither change nor a relationship for the effects of swelling on spinal reflex excitability. In this regard, our current findings, along with previous studies [ 12 , 13 , 43 ], indicate that underlying neural mechanism associated with AAS symptom severity does not appear to be directly related to alterations in spinal reflex excitability.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous investigations [ 12 , 13 ] with AAS patients found neither change nor a relationship for the effects of swelling on spinal reflex excitability. In this regard, our current findings, along with previous studies [ 12 , 13 , 43 ], indicate that underlying neural mechanism associated with AAS symptom severity does not appear to be directly related to alterations in spinal reflex excitability.…”
Section: Discussionsupporting
confidence: 71%
“…However, the current study did not confirm any links between neural changes and severity of acute symptoms. The lack of associations may be supported by a recent systematic review, concluding that the presence of clinical pain does not influence H-reflex responses [ 43 ]. With regards to the effects of ankle swelling on spinal reflex excitability, a previous investigation [ 15 ] using simulated ankle joint effusion model showed alterations in H-reflex measures of ankle stabilizing muscles.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as experimental pain could alter the motor output in target and not target muscles (48)(49)(50)(51), the migraine attack could constitute a nociceptive input able to alter the motor control of neck muscles leading to a reduction in cervical mobility. As the effect of clinical pain on motor output is less consistent (51)(52)(53), and no study that we are aware of ever assessed the effect of migraine-like pain on cervical motor output, future studies should assess the mechanisms by which migraine-like pain affects the cervical motor output. Even if changes in mechanical behaviors occurring during acute pain could have a short-term benefit, they often cause long-term mechanical consequences, as increased muscle stiffness and reduced movement variability (54).…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with the findings of this study which found no consistent evidence that experimental pain inhibits cortical changes associated with motor learning. Sub-grouping analysis performed by Sanderson et al [ 71 ] suggests that the impact of pain on cortical excitability may be dependent on the specific pain paradigm or tissue stimulated. The authors reported increased cortical excitability when hypertonic saline was injected into non-contractile tissue and a decrease when injected into contractile tissue.…”
Section: Discussionmentioning
confidence: 99%